Bleeding as a complication of fine needle lung biopsy. Issue 12 (December 1988) - Doyle, T; Mullerworth, M
Abstract : Two patients in whom bleeding into the pleural space was a major complication of fine needle biopsy of the lung are described. Both had a pleural effusion before biopsy.